WENNER'S CONFIGURATION GEOELECTRIC METHOD FOR THE INTERPRETATION OF THE SUBSURFACE STRUCTURES OF PANUNGKIRAN VILLAGE - Aulia Farihanum; Nazaruddin Nasution; Abdul Halim Daulay (Universitas Islam Negeri Sumatera Utara Medan, 2020)
A research has been carried out which aims to determine the subsurface structure using the geoelectric method in Panungkiran Village, Kab. Deli Serdang, Prov. North Sumatra Geoelectric data retrieval uses the Wenner configuration to determine the distribution and depth of subsurface structures in Panungkiran Village, Deli Serdang Regency. Prov. North Sumatra Data collection is 1 track with a length of 90 meters, Data processing in the study using MS office software Excel Notepad, and RES2DINV The results of the measurements consist of several types which are distinguished based on the range of resistivity values, namely in the range of 34.0-3188 2m interpreted by lithological layers topsoil (34.0-65.1 Ωm), sandstone (65.1-1252 Ωm) weathered travertine limestone (125-456 Ωm), fresh trvertine limestone (456-3188 Ωm), and resistivity >3188 Qm is interpreted as a cave at a depth of 9-12 meters.